Influence of Agro-Industrial Leachate Polluted Soil on the Compressive and Flexural Properties of Unstressed Concrete Substructure - Adewuyi , Adekunle P. (Research and Developments in Engineering Research Vol. 9, 2023)
In terms of compressive and flexural strengths as well as load-carrying capabilities, this work compares the short-term behavior of concrete substructures situated in cyanide-contaminated soil to those in naturally unpolluted soils. Agriculture, energy, transportation, building, technology, and mining are just a few of the several industrial activities that have increased as a result of the ongoing rise of the human population. These, in turn, exacerbate soil pollution by lowering the mechanical and physical qualities of the soil, such as electrical conductivity, bulk density, pH, moisture content, and hardness. This results in a loss of crop diversity, productivity, and soil quality. The rate of deterioration concrete substructure is initiated by growth of salt crystals inside concrete pores beneath the surface layer based on the chemical properties of the soil and groundwater. The aim of this study was to investigate the effects of cassava mill effluent-polluted soils on the compressive and flexural strengths concrete substructure elements. The cubes' compressive strengths were evaluated every seven days until day 84, but the beams were only put through third-point loading flexural testing at that time. Concrete test specimens' compressive strength rose in both soil settings, however the trend in the contaminated soil was less pronounced. Between the 7th and 28th days, the strength decreased by 2.50 to 9.47%, but it lost strength continuously between the 28th and 84th days, losing 9.95% (COV = 2.64%). The load-deflection curves were quadratic for the beams in the two geo-environments. The beams in cyanide-polluted soil lost 34.5% of its flexural stiffness, while its loss of load-carrying capacities at the first crack and ultimate failure were 15.8 and 20% respectively. Higher degree of deterioration is certain for loaded concrete substructures in similar conditions. Hence, prior knowledge of soil chemistry is crucial to determining suitable concrete grade and nominal cover for durable substructural elements.